A Selective Excited‐State Intramolecular‐Proton‐Transfer (ESIPT) Sensor for Copper(II) Based on Chelation‐Enhanced Quenching and "Off‐On" Detection of Amino Acids. Issue 25 (23rd March 2023) - Devasia, Jyothis; Joy, Francis; Nizam, Aatika
Abstract: We report the synthesis of 2‐(4, 5‐diphenyl‐1H‐imidazole‐2‐yl)phenol (TPI‐9 ) as an interesting fluorescent molecule displaying Excited‐State Intramolecular‐Proton‐Transfer (ESIPT) with stokes shift of 120 nm. Phenolic compounds with the ability to form intramolecular hydrogen bonds and subsequent proton transfer are known as ESIPT fluorophores. Proton accepting ability can increase significantly by tailoring electron‐donating groups. With the assistance of an environment‐friendly organocatalyst, 10‐camphor sulfonic acid (10‐CSA), TPI‐9 was synthesized to introduce substituents with electron‐donating abilities to develop an efficient ESIPT mechanism. Factors influencing the emission, such as solvent, pH, and metal ions, are investigated. Quenching of fluorescence by Cu 2+ through chelation enhancement quenching effect with a high selectivity allowed the establishment of a Cu 2+ sensor with an LoD of 0.57 ppm and a ratiometric estimation with an LoD of 0.73 ppm. Metal binding (2 : 1) stoichiometry and quenching constant (0.0072 mol −1 s −1 ) are calculated from Job's and Stern‐Volmer plots. Density functional theory (DFT) calculations are in accordance with the experimental results. Competitive replacement of TPI‐9 by amino acids restores ESIPT, consequently, the fluorescence. Thus, an "off‐on" fluorescence sensor for amino acid estimation is developed under 1 minute incubation. A linear relationship between amino acid concentration and fluorescence intensity is in 0‐20 μg/mL range, and the LoD is less than 2.2 μg/mL. Abstract : Synthesis of 2‐(4, 5‐diphenyl‐1H‐imidazol‐2‐yl) phenol using 10‐CSA catalyst. ESIPT fluorescent property of the molecule with a large stokes shift of 120 nm. Estimation of copper (II) through fluorescent quenching and ratiometry. A novel method for the estimation of amino acids by competitive reversion of the fluorescence.